(untitled) (Global Journals of Research in Engineering, 2014)
The experience of the use of bituminous concrete upstream facing is presented in Algeria in the four big dams: Ghrib (1926-1938), Bouhnifia (1930-1941), Sarno (1947-1954) and Ighil Emda, The problem posed in the aroused dams is especially delicate because of the instability of the mask which could become precarious to the temperature. Therefore it was covered with a thermal protection, which demands a periodic renovation. This solution was very expensive. To avoid these costs, one tried to test the stability of the mask without the thermal protection. One prepared a reduced sample of the mask of bouhnifia dam. Then, one put this sample on an inclined facing of 1/1 (slope of the dam); and maintained it in an oven during more than 48 hours under a temperature of 70 C#xB0;. This experience permitted to determine that the sample kept its initial shape. The gotten results confirmed that the mask of the Bouhnifia dam can resist the action of the temperature without the necessity of the thermal protection.